Higher Disability in Women Than Men Scheduled for Total Knee Arthroplasty for Degenerative Osteoarthritis: A Cross‐Sectional Analysis From India. Issue 6 (9th May 2020) - Devasenapathy, Niveditha; Malhotra, Rajesh; Mittal, Kanchan; Garg, Bhavuk; Kumar, Vijay; Zodpey, Sanjay; Dogra, Hardik; Maddison, Ralph; Belavy, Daniel L.
Abstract : Objective: Higher level impairments and activity limitation among those scheduled for total knee arthroplasty (TKA) is known. Sex differences in participation restriction which is the final domain of disablement pathway is not known. No data from developing countries exist on sex differences in disability levels at the time of TKA. Methods: In a cross‐sectional analysis of 240 patients (188 women; 72 men) scheduled for TKA, impairment (pain, symptoms, quadricep muscle strength, and knee range of motion [ROM]), activity limitation (self‐reported and objective performance‐based measurements), and participation restriction were compared. Multivariable regression analyses were used to adjust for key sociodemographic and clinical characteristics. Associations between impairments and participation restriction were analyzed. Results: Compared with men, women were more likely to have higher levels of impairment (knee injury and osteoarthritis outcome pain score adjusted mean difference [aMD]: −6.9 [95% confidence interval CI −13.7 to −0.18]; flexion ROM of less than 100° adjusted odds ratio: 5.7 [95% CI 1.6‐20.3]; and 36% lower muscle strength [95% CI 24%‐49%]) and lower objectively measured functional ability (walking speed aMD: −0.12 m/s [95% CI −0.23 to −0.02]; stair climbing time aMD: 9.5 s [95% CI 1.5‐17.5]). Participation restriction was higher in women compared with men. Of the impairment measures (pain, ROM, and muscle strength), pain contributed to participation restriction in both sexes. Conclusion: This study demonstrated higher levels of disability in women than in men at the time of TKA. Effect of pain on participation restriction was higher compared with muscle strength and ROM. Evidence of delay in decision‐making to undergo TKA and reasons for delay need to be studied specifically in the context of lower middle–income countries.